The Avengers. Vol. 2, Twilight dreaming - MacKay, Jed, 1983- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2024)
"What has happened to the Avengers? They are Earth's Mightiest Heroes - but they're beginning not to recognize Earth as their own. Trapped in a world they never made, the team must struggle to break free - while one of their number fights their own hopeless battle against Myrddin and his Twilight Court! But Avengers never fight alone, and their most dangerous member is about to join the conflict. At stake: the fate of Kang the Conqueror! With Kang being the only source of information the Avengers have regarding the Tribulation Events, can the Avengers save him before Myrddin strikes? Plus: The Avengers' orbital super-fortress, the Impossible City, just isn't quite home without Edwin Jarvis! Collecting AVENGERS (2023) #7-11." --